IEEE 802.15.4 based topology control and routing for mobile Sink wireless sensor networks - TONG Jie1; YANG Fan2; QIAN De-pei1 (Tongxin xuebao)
Based on the standard of IEEE 802.15.4b,a cross-layer protocol design combining cluster-tree formatting and mobile routing was proposed for query-driven wireless sensor networks with mobile Sink（s）.Firstly,energy consumption,network connectivity,load balancing and sub-tree depth were employed as the evaluation factors.A topology evaluation function under a multi-objective optimization model was defined to construct the stable and optimal underlying clus-ter-tree network.Secondly,the beacon frame scheduling based distributed sleep synchronization algorithm in IEEE 802.15.4 MAC was improved,which was used to maintain the network synchronization and topology correction on low duty-cycle.Thirdly,the parent-child relationships established during the topology formatting according to "first beacon","best links","top level" rules were exploited to build the two-way routing paths between mobile Sink（s） and the nodes within N-Hop range.Eventually,the topology control schemes at MAC layer and the query routing approach at network layer were completely implemented in the protocol stack of TinyOS.The experimental results show that the evaluation function can effectively reflect the quality of network formatting.Jointed with the sleep synchronization mechanism un-der the topology generated using the rule of "best links",the N-Hop reactive routing exhibits high energy-efficiency.